Elmer the elephant : story by Georgeanne Irvine ; photographs by Ron Garrison. - Irvine, Georgeanne (Chicago : Children's Press, 1983)
A baby elephant enjoys playing with the other young elephants at the zoo, looking forward to the time when he will be fully grown and weigh 12,000 pounds.
Keywords: Elephants; Animal babies